KONFLIK BATIN TOKOH DALAM NOVEL AKU TAK MEMBENCI HUJAN KARYA SRI PUJI HARTINI: KAJIAN PSIKOLOGI SASTRA - Dikha Ayu Sepianti; Maizar Karim; Ade Bayu Saputra (STKIP Subang, 2026)
This research focuses on the Inner Conflict of Characters in the Novel I Do Not Hate The Rain by Sri Puji Hartini: A Study in Literary Psychology. This research aims to describe the forms of inner conflict in the novel I Do Not Hate The Rain by Sri Puji Hartini using a literary psychology approach. The theory used in this research is Kurt Lewin's theory. The type of research used in this study is qualitative with a descriptive method. The data source used in this research is the novel I Do Not Hate The Rain by Sri Puji Hartini, with data in the form of sentences consisting of novel excerpts in the form of dialogues between characters, monologues, and author narratives. The results of the research show that there are three forms of inner conflict according to Kurt Lewin's theory: approach-approach conflict, avoidance-avoidance conflict, and approach-avoidance conflict.